THE EFFECTIVENESS OF MUSIC THERAPY IN REDUCING ANXIETY IN THIRD TRIMESTER OF PREGNANCY - Eti Salafas; Puji Lestari; Moneca Diah Listiyaningsih (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
The average anxiety experienced by third-trimester pregnant women is higher than the first and second trimester. Anxiety increases as the gestational age get older. If this condition had not to handle, it could impact on pregnancy and during labour. Efforts to overcome anxiety can be made with music therapy. This therapy is therapy without drugs by playing music to pregnant women. Song rhythm, harmony, and beat 60 beats per minute can make the mother calm. The purpose of this study was to determine the level of anxiety of pregnant women before and after the intervention, then analyze the effectiveness of music therapy in reducing anxiety levels. The method used is a quasi-experiment. The population in this study was third-trimester pregnant women in the Ambarawa Puskesmas area with samples taken by purposive sampling of 30 respondents. Data collection carried out in August 2019. The data not normally distributed, so the analysis carried out using the Wilcoxon test with the results that there were different levels of anxiety before and after treatment with music therapy (p = 0.001). The average anxiety score after being given music therapy dropped to 4.47 from 9.53, although it was still in the mild anxiety category. It can be concluded that music therapy is effective in reducing the anxiety level of pregnant women in the third trimester. Music therapy recommended being applied in the management of anxiety on pregnant women in the third trimester. Key Words: Anxiety Level, Music Therapy, Third-trimester, Pregnant Women